2020
DOI: 10.1111/bcpt.13513
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy and safety of different doses of nifekalant in the instant cardioversion of persistent atrial fibrillation during radiofrequency ablation

Abstract: Nifekalant has been used in the treatment of atrial arrhythmia recently. However, there is no consensus on the preferable nifekalant dose to treat atrial fibrillation (AF). The purpose of this study was to explore efficacy and safety of different doses of nifekalant in the cardioversion of persistent AF. The study was a single‐centre, randomized controlled trial. All subjects received nifekalant or placebo intravenously, and the nifekalant was given at the dosage of 0.3, 0.4 or 0.5 mg/kg. Primary efficacy end‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…A total of 37 of these were further excluded for various reasons, such as insufficient data and inappropriate controls. Finally, 405 articles were excluded and 12 research studies met all the inclusion criteria (10,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). A flow chart of the study selection process is shown in Fig.…”
Section: Results Of the Article Searchmentioning
confidence: 99%
“…A total of 37 of these were further excluded for various reasons, such as insufficient data and inappropriate controls. Finally, 405 articles were excluded and 12 research studies met all the inclusion criteria (10,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). A flow chart of the study selection process is shown in Fig.…”
Section: Results Of the Article Searchmentioning
confidence: 99%